2016
DOI: 10.2298/jas1604399a
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of an electronic wallet system and determinants of cassava farmers’ participation in off-farm activities in Abuja, Nigeria

Abstract: This study assessed an electronic wallet (e-wallet) system and determinants of cassava farmers' participation in off-farm activities in Abuja, Nigeria. A sample of 67 cassava farmers was selected through a multi-stage sampling technique from six selected agricultural extension blocks. Primary data were used. Data were collected using a well-structured and well-designed questionnaire. The analytical tools used were descriptive statistics and maximum likelihood estimates using the logistic regression model. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…Therefore, an increase in the level of education, exposes a farmer to be profit-oriented and struggle to lower the transactional costs of marketing. The results are also in agreement with Alabi et al (2016) who reported that it is more likely for the more educated farmers to work off the farm which will enhance their level of productivity that will make them choose a profitable market outlet. Farm size influenced the choice of market outlet negatively for the local market and was significant at (P<0.10).…”
Section: Resultssupporting
confidence: 90%
“…Therefore, an increase in the level of education, exposes a farmer to be profit-oriented and struggle to lower the transactional costs of marketing. The results are also in agreement with Alabi et al (2016) who reported that it is more likely for the more educated farmers to work off the farm which will enhance their level of productivity that will make them choose a profitable market outlet. Farm size influenced the choice of market outlet negatively for the local market and was significant at (P<0.10).…”
Section: Resultssupporting
confidence: 90%
“…The study was carried out at the Federal Capital Territory, Abuja Nigeria. Geographically, it is located at latitude 9 o 4 l 20.1504 ll N and longitude 7 o 29 l 28.6874 ll E. (Olugbenga, et al, 2016). It is bounded in the North by Kaduna state, in the West by Niger State, in the East by Nasarawa State and in the South by Kogi State; and is made up of six (6) Area Councils namely; Gwagwalada, Kuje, Kwali, Bwari and Abuja Municipal.…”
Section: Materials and Methods The Study Areamentioning
confidence: 99%